Pelatihan Pembuatan Jamu Kunyit Asam dan Beras Kencur Instan di SMK Harapan Massa Depok - Wenas, Desy Muliana; Setyaningsih, Erwi Putri; Kusuma, Ika Maruya; Pratiwi, Ritha Widya; Hasanah, Kurniatul; Bahri, Saiful (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Jamu is an ancestral heritage of the Indonesian people that has important health benefit. Kunyit Asam (turmeric and tamarind) and Beras Kencur (rice and aromatic ginger) are two types of jamu that can help maintain and improve the health of adolescent students. This community service activity aims to help the students of SMK Harapan Massa understand how to make turmeric-tamarind and rice-kencur instant herbal drinks, as well as to grasp their uses and benefits. Method: Fifty-eight respondents participated in a training session focused on making instant kunyit asam and beras kencur. The questionnaire is used as a benchmark to measure the knowledge level of the students at SMK Harapan Massa. Results: There was an increase in questionnaire scores, indicating an improvement in the knowledge of respondents who completed both the pre-test and post-test, such as 87% (pre-test) menjadi 90% (post-test). Conclusions: The jamu workshop had enhance the students' knowledge and understanding of the benefits, preparation, production, and safe consumption methods of jamu.